2020
DOI: 10.3390/plants9101396
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological, Microanatomical and Molecular Cytogenetic Characterization of the Medicinal Plant Chelidonium majus L.

Abstract: Chelidonium majus L. is a medicinal plant well-known as a valuable source of isoquinoline alkaloids, which has a variety of pharmacological properties including anti-viral and anti-bacterial effects. However, considerable intraspecific bio-morphological variability in C. majus complicates raw material identification and verification. For the first time, we have brought into cultivation five populations of C. majus subsp. majus originated from different regions, and performed their agro-morphological, microanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Wide variation in the alkaloid content in C. majus has been reported previously by other authors [ 18 , 27 , 28 ]. Many factors, such as genotype, plant age, developmental phases, harvesting time, and environmental conditions, can affect the alkaloid content in raw plant material.…”
Section: Resultssupporting
confidence: 71%
“…Wide variation in the alkaloid content in C. majus has been reported previously by other authors [ 18 , 27 , 28 ]. Many factors, such as genotype, plant age, developmental phases, harvesting time, and environmental conditions, can affect the alkaloid content in raw plant material.…”
Section: Resultssupporting
confidence: 71%
“…Cytogenetic studies are important in taxonomic studies because each species has a different number and structure of chromosomes (Bolcun-Filas and Schimenti, 2012). Cytological studies play a role in studying the presence of morphological abnormalities (Samatadze et al, 2020), studying evolutionary processes (Lusinska et al, 2019), identification (Lukhtanov and Shapoval, 2017) and to study the diversity of a species (Bzdega et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some karyotypes, small variations in the size of the 45S rDNA and 5S rDNA clusters were observed. It has previously been reported that the copy number of rRNA genes could slightly vary in different plant populations, which could be related to intraspecies diversity [ 51 , 52 ]. At the same time, considerable chromosome abnormalities such as chromosome rearrangements or aneuploidy were not revealed in the studied plants, indicating the relative stability of their karyotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For fluorescent in situ hybridization (FISH) assays, the chromosome spread preparations were made as described previously with minor modifications [ 52 ]. Seeds were germinated in Petri dishes on the moist filter paper at RT.…”
Section: Methodsmentioning
confidence: 99%